Concurrent transmission mechanism to mitigate pan-exposed-node problems in wireless sensor networks - Xuejian Zhao; Siguang Chen; Jing Guo; Han Hu; Zhixin Sun (International Journal of Distributed Sensor Networks)
Power control technology is widely used in wireless sensor networks to improve network performance. The asymmetric transmission power strategy used in power control technology causes the re-emergence of hidden-node problems and more serious exposed-node problems. This article analyzes the reasons of these problems and proposes the concept of the pan-hidden node and pan-exposed node. To avoid pan-hidden-node problems and mitigate pan-exposed-node problems, a concurrent transmission mechanism is presented. The concurrent transmission mechanism contains a strict time schedule for different categories of frames and an interference degree criterion to ensure concurrent transmission. The rigorous time schedule can guarantee that different classes of frames do not interfere with one another. The interference among the frames of the same type is constrained by the interference degree criterion. Finally, the performance of the concurrent transmission mechanism is evaluated using simulation experiments.